205 PI3K-epigenetic 'metagene' alterations were associated with PFS but appear independent of FIGO-2018 stage in cervival patients enrolled in the prospective european bioraids study. (18th September 2019) - Scholl, S; Rouzier, R; Fourchotte, V; Kenter, G; Popovic, M; Dureau, S; Kamal, M
Abstract : Objectives: The RAIDs consortium (www.raids-fp7.eu), conducted a prospective cervical cancer study, [BioRAIDs (NCT02428842 )]. The clinical and biological dataset included 419 patients from 18 centers in 7 EU countries (Ngo et al, 2015; Samuels et al, 2016 and Scholl et al, in press). Objectives were to stratify patient populations and identify molecular patterns associated with poor outcome. Methods: Magnetic resonance imaging (MRI) was a mandatary inclusion criterium. We compare treatment sequences administered according to FIGO stage at inclusion in comparison to ideal treatment sequences according to the more recent FIGO 2018 staging, if lymph node (LN) positive patients are upstaged to stage IIIC. Furthermore, the molecular alterations of a 'metagene' associated with outcome are analyzed as a function of FIGO stage. Results: Sequence of treatments received up to 6 months are reported according to FIGO-2018 stage. At a median follow up of 24 months, progression-free survival (PFS) rates of the BioRAIDs population, treated by chemoradiation (87%) as first or follow on treatment, were 67% [CI95%: 61.9–72.5]. We show evidence that a selection of frequent deleterious variants regrouped in a 'metagene' were associated with outcome (PFS) yet appeared independent of FIGO-2018 stage. Conclusions: In 2013, treatment guidelines allowed radical surgery or chemoradiation for clinical stage IB2 disease. In case of pretreatment suspicion of tumour spread to pelvic lymph nodes (FIGO-2018 staging: IIIC1) many centers now perform primary chemoradiation We were not able to show the set of molecular markers previously associated with poor outcome to be also associated with FIGO stage.